THE USE OF ANIME FAN FICTION STORY AS A MEDIA WITH VSS TECHNIQUE TO IMPROVE THE TENTH GRADERS’ VOCABULARY (RETAIN, 2015)
Abstract Mastering in vocabulary is more specifically predictive and reflective of high levels of reading achievement. But, reading is not a habit yet in Indonesia because the learners’ interest are low. Recently, there has been recognition that young people are able to engage in media in variety of ways, such as Anime Fan Fiction. And there is a technique of teaching vocabulary that can engage the learners in their own learning, an interactive learning that promotes word conciousness named VSS. Thus, this study was conducted to describe the new framework of the implementation and prove the learners’ improvement of their vocabulary through reading Anime FanFiction with VSS technique. The objectives of this study were to show and describe how was the implementation of VSS technique for teaching vocabulary in contexts. To find out and prove that the learners have improved their vocabulary mastery after being taught using VSS technique in their reading class. This study was one group pre-posttest design which involved one class of the tenth graders at SMKN 6 Surabaya, the English teacher of the class and the 31 learners. This study was applied in two meetings on May, 7th and 13th, 2015. The data are taken by tthe observation checklist and the result of pre-posttest score. The findings showed that the score of the posttest was higher than the pretest. Then for the treatment, at the first meeting, the learners still faced the difficulty follow in step in analyzed vocabulary of VSS chart. Meanwhile, they could follow all the steps easily in the second meeting. So, this study was successful to improve the vocabulary through reading Anime Fan Fiction as a media with VSS technique. Key Words: Vocabulary, VSS, Anime, Fan Fiction Abstrak Menguasai perbendaharaan kata secara spesifik lebih dipredikisi dan direfleksi dari tingginya tingkat prestasi dalam membaca. Tetapi, membaca belum menjadi kebiasaan di Indonesia karena ketertarikan para murid dalam membaca rendah. Dewasa ini, ada sekian banyak pengakuan bahwa remaja dapat terikat oleh media dalam berbagai cara, seperti Anime Fan Fiction.Dan ada sebuah teknik pengajaran kosakata yand dapat mengikat para murid dalam pembelajarannya sendiri, sebuah pembelajaran interaktif yang memgutamakan pemahaman kata yaitu VSS. Oleh karena itu, study ini diadakan untuk mendeskripsikan implementasi dari desain mengajar yang baru dan membuktikan peningkatan kosakata para murid dengan membaca Anime Fan Fiction dengan pengajaran VSS teknik. Tujuan dari studi ini yaitu menunjukkan dan menjelaskan bagaimana implementasi dari VSS teknik sebagai pengajaran kosakata dalam konteks. Dan, membuktikan bahwa mereka telah meningkatkan kosakata setelah diajarkan dengan teknik VSS di kelas mereka. Studi ini ialah Quantitaive, pre-posttest dengan satu grup yang melibatkan satu kelas dari tingkat 10 di SMKN 06 Surabaya, guru bahasa inggris dikela itu, dan 31 murid. Studi ini diaplikasikan dalam dua kali pertemuan pada tanggal 07 dan 13 Mei 2015. Data dari studi ini diambil dari hasil observasi dan hasil score test. Dari studi ini ditemukan bahwa score posttest lebih tinggi dari pretest. Lalu untuk pengaplikasian studinya, para murid masih mengalami kesulitan di peretemuan awal. dalam mengikuti arahan dari peneliti untuk menganalisis kosakata dengan VSS teknik Setelah itu, mereka dapat mengikuti arahan dari peneliti dengan baik di pertemuan kedua. Jadi, studi ini berhasil dalam meningkatkan kosakata melalui membaca Aniime Fan fiction sebagai medianya dengan VSS teknik. Kata kunci: Kosakata, VSS, Animasi, Fan Fiction